Carbamazepine solubility enhancement in tandem with swellable polymer osmotic pump tablet: A promising approach for extended delivery of poorly water-soluble drugs - Hadjira Rabti; Jumah Masoud Mohammed Salmani; Eltayeb Sulimen Elamin; Narimane Lammari; Jie Zhang; Qineng Ping (Elsevier, 2014)
Elementary osmotic pump (EOP) is a unique extended release (ER) drug delivery system based on the principle of osmosis. It has the ability to minimize the amount of the drug, accumulation and fluctuation in drug level during chronic uses. Carbamazepine (CBZ), a poorly water-soluble antiepileptic drug, has serious side effects on overdoses and chronic uses. The aim of the present study was to design a new EOP tablet of CBZ containing a solubility enhancers and swellable polymer to reduce its side effects and enhance the patient compliance. Firstly, a combination of solubilizing carriers was selected to improve the dissolution of the slightly soluble drug. Then, designing the new EOP tablet and investigating the effect of different variables of core and coat formulations on drug release behavior by single parameter optimization and by Taguchi orthogonal design with analysis of variance (ANOVA), respectively. The results showed that CBZ solubility was successfully enhanced by a minimum amount of combined polyvinyl pyrrolidone (PVP K30) and sodium lauryl sulfate (SLS). The plasticizer amount and molecular weight (MW) together with the osmotic agent amount directly affect the release rate whereas the swellable polymer amount and viscosity together with the semi-permeable membrane (SPM) thickness inversely influence the release rate. In addition, the tendency of following zero order kinetics was mainly affected by the coat components rather than those of the core. Further, orifice size does not have any significant effect on the release behavior within the range of 0.1 mm to 0.8 mm. In this study we report the successful formulation of CBZ-EOP tablets, which were similar to the marketed product Tegretol CR 200 and able to satisfy the USP criterion limits and to deliver about 80% of CBZ at a rate of approximately zero order for up to 12 h.